LIKUIDITAS, STRUKTUR ASET, KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL TERHADAP STRUKTUR MODAL DENGAN FIRM SIZE SEBAGAI MODERASI - Richard Julian; Herman Ruslim (Fakultas Ekonomi Universitas Tarumanagara, 2024)
on capital structure with firm size as a moderating variable. This study uses a quantitative method by taking apopulation of companies listed on the Indonesia Stock Exchange (IDX) in the property sector. The sample wasselected by purposive sampling technique in order to obtain a sample of 17 property companies. The data analysismethod used is multiple regression analysis and moderation regression analysis using the SPSS 25 test tool. Theresults show that liquidity has a negative effect on capital structure, asset structure has a negative effect on capitalstructure, managerial ownership has a positive effect on capital structure, and managerial ownership has a positiveeffect on capital structure. The proven moderation test results are firm size significantly moderate the relationshipbetween institutional ownership and capital structure.